2021
DOI: 10.26508/lsa.202000961
|View full text |Cite
|
Sign up to set email alerts
|

A role for condensin in mediating transcriptional adaptation to environmental stimuli

Abstract: Nuclear organisation shapes gene regulation; however, the principles by which three-dimensional genome architecture influences gene transcription are incompletely understood. Condensin is a key architectural chromatin constituent, best known for its role in mitotic chromosome condensation. Yet at least a subset of condensin is bound to DNA throughout the cell cycle. Studies in various organisms have reported roles for condensin in transcriptional regulation, but no unifying mechanism has emerged. Here, we use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…4 B and S3 C). Notably, such suppression went well beyond the reduction in Pol II recruitment and nascent transcription that typically occurs in response to thermal stress at housekeeping genes ( 34 , 35 ). Collectively, the results indicate that loss of Pol II recruitment and/or Pol II retention within chromatin underlies the cessation of transcription.…”
Section: Resultsmentioning
confidence: 99%
“…4 B and S3 C). Notably, such suppression went well beyond the reduction in Pol II recruitment and nascent transcription that typically occurs in response to thermal stress at housekeeping genes ( 34 , 35 ). Collectively, the results indicate that loss of Pol II recruitment and/or Pol II retention within chromatin underlies the cessation of transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Cohesin, together with CTCF plays a major role in the formation of topologically associated domains (TADs), as well as in intra-TAD interactions. In addition, recent studies have found that condensin regulates gene expression 32 , 33 . The chromatin decondensation that accompanies HCV infection, as seen here, is consistent with the idea that HCV-induced changes in cohesin localization are due to major changes in TAD formation and inter-TAD interaction in the host cell genome which would most likely alter chromatin structure.…”
Section: Discussionmentioning
confidence: 99%
“…Condensin-mediated genomic contacts are formed by loop extrusion and diffusion capture mechanisms (Ganji et al, 2018; Kim et al, 2020; Tang et al, 2023). Condensin function is associated with gene regulation (Crane et al, 2015; Dowen et al, 2013; Hocquet et al, 2018; Iwasaki et al, 2019; Lancaster et al, 2021; Li et al, 2015; Swygert et al, 2019). Although it has been shown that CTCF plays a significant role in the formation of TADs and cohesin loops, the factors that participate in the formation of condensin-mediated genomic contacts and domains remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%